Application of Copywriting Strategy in Brodo Active Commercial Video Production - Wirabumi, Arya Wibowo; Nugrahani, Rah Utami; Priastuty, Chairunnisa Widya (ARRUS Journal of Social Sciences and Humanities, 2024)
The creative industry in Indonesia has developed very rapidly, it is shown that the creative economy in Indonesia contributes 7.5% of Indonesia's gross domestic product (GDP). One of the creative industries that is developing very rapidly is the fashion industry. Brodo is a fashion company that was founded in 2010 and initially operated in the leather shoe sector, and now has expanded its reach by having a new section on sports shoes. Brodo itself is one of the companies that has carried out digital marketing to introduce the products they have. One type of digital marketing they have is commercial advertising videos. At the end of 2023, Brodo will launch 2 of their sports shoe products, namely Brodo Mezzala and Inizio Running, which do not yet have an introductory video to market their products in the form of commercial advertising videos. Therefore, the researcher conduct research entitled "Application of Copywriting Strategy in the Production of Brodo Active Commercial Advertising Videos". The theory used by the researcher in this research is copywriting theory with several supporting indicators to be able to represent and provide an interesting message to the audience. To be able to obtain data as a basis for this research, the researcher conducted observations, interviews and questionnaires. The object of this researcj has a duration of one minute and three seconds with the title "Brodo Active Perfomance – Mulai Bergerak" as a commercial advertising video which aims to be an introductory video for Brodo Mezzala and Inizio Running.